Interferon system deficiencies exacerbating severe pandemic virus infections - Stertz, Silke (Trends Microbiol, 2021)
Pandemics are caused by novel pathogens to which pre-existing antibody immunity is lacking. Under these circumstances, the body must rely on innate interferon-mediated defenses to limit pathogen replication and allow development of critical humoral protection. Here, we highlight studies on disease susceptibility during H1N1 influenza and COVID-19 (SARS-CoV-2) pandemics. An emerging concept is that genetic and non-genetic deficiencies in interferon system components lead to uncontrolled virus replication and severe illness in a subset of people. Intriguingly, new findings suggest that individuals with autoantibodies neutralizing the antiviral function of interferon are at increased risk of severe COVID-19. We discuss key questions surrounding how such autoantibodies develop and function, as well as the general implications of diagnosing interferon deficiencies for personalized therapies.